Sociétés chorales et Renaissance de la musique anglaise, 1840-1910 - Gilles Couderc (Cahiers Victoriens et Edouardiens, 2010)
The great English choral tradition as we know it today was born along with the Industrial Revolution with the development of choral societies like the oldest, the Halifax Choral Society in 1817, while the Birmingham Choral Society, founded in 1843, was to provide a chorus for the town’s Triennial Music Festival. Those societies were fostered so as to tame, civilise and educate the potentially unruly new unskilled labour force who manned “the dark Satanic mills” of the expanding northern industrial cities and to lead them away from drink or the profanities of the nascent music-halls. Their favourite repertoire was the English oratorios of Handel and Mendelssohn, a genre which flourished all century long in the wake of the great religious awakening of the late eighteenth century and provided English and foreign composers with work in an opera-shy kingdom. Various social reformers, like John Curwen of Tonic Sol-Fa fame, developed methods to teach the untrained choristers how to read music, thus permitting their exposure to high-brow culture, to which the policy of the music publisher Novello greatly contributed. Paradoxically, the Renaissance of English music in the late 19th century benefited from the craze for choral singing but also somehow triggered its demise when native composers, who had assimilated the lessons of their foreign competitors and raised their standards of composition, required more from their amateur choristers, gradually forced to give up in favour of professionals, increasing the gap between popular and high brow culture.